SNP rs688 within the low‐density lipoprotein receptor (LDL‐R) gene associates with HCV susceptibility - Steba, Gaby S. (Liver Int, 2018)
BACKGROUND & AIMS: Despite high‐risk behaviour, 10%‐20% of HCV multiple exposed individuals remain uninfected (MEU), whilst the remainder become infected (MEI). We hypothesize that host factors play a role in HCV susceptibility. We aimed to identify polymorphisms in host genes that encode for proteins involved in viral entry: CD81, Scavenger receptor 1 (SR‐1), Low‐density lipoprotein receptor (LDL‐R), Claudin‐1 (CLDN1), Occludin (OCLN) and Niemann‐Pick C1–like 1 (NPC1L1). METHODS: Multiple exposed infected and MEU from two observational cohorts were selected. From the MSM study of acute infection with HCV (MOSAIC), HIV‐1 infected MEU cases (n = 30) and HIV‐1 infected MEI controls (n = 32) were selected based on reported high‐risk behaviour. From the Amsterdam Cohorts Studies (ACS) injecting drug users (IDU) cohort, MEU cases (n = 40) and MEI controls (n = 22) were selected who injected drugs for ≥2 years, in the nineties, when HCV incidence was high. Selected single nucleotide polymorphisms (SNPs) were determined by sequencing or SNP assays. RESULTS: No associations were found for SNPs within genes coding for CD81, SR‐1, Claudin‐1 or Occludin between the MEU and MEI individuals from either cohort. We did observe a significant association for rs688 within the LDL‐R gene with HCV infection (OR: 0.41 P = 0.001), however, LDL cholesterol levels did not vary between individuals carrying the differential SNPs. Additionally, a marginal significant effect was found for rs217434 and rs2072183 (OR: 2.07 P = 0.032 and OR: 1.76 P = 0.039, respectively) within NPC1L1. CONCLUSIONS: Our results demonstrate that the rs688 SNP within the LDL‐R gene associates with HCV susceptibility through mucosal as well as intravenous exposure.